2007
DOI: 10.2174/092986707781058959
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, Oxidative Stress and Cardiovascular Diseases-Do Anti-Oxidative Therapies Fail?

Abstract: Oxidative reactions caused by cigarette smoke (CS) chemicals have been shown to initiate crucial events in atherogenesis. However, physicians and scientists are confronted with the paradoxical situation that an antioxidative treatment of smokers improves acute smoking effects but hardly has any impact on long term outcome of cardiovascular diseases (CVD). In this review we make an attempt to explain this paradox. First, smoke-derived free radicals and oxidants are part of CS causing a pro-oxidative state in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 103 publications
3
47
0
1
Order By: Relevance
“…50 The shift to a pro-oxidative, hence, NO level-reducing environment in the vascular wall of smokers is further facilitated by the deposition of oxidation catalyzing metals in cigarette smoke, as well as by an alteration in the balance between of oxidantgenerating and oxidant-reducing cellular systems, in favor of the former. 51,52 Macrophages, neutrophils, the mitochondrial respiratory chain, and xanthine oxidases are major sources of the increased levels of oxidants in the vascular wall of smokers. Furthermore, stable aldehydes in cigarette smoke increase reactive oxygen species production by the activation of NADPH oxidases.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…50 The shift to a pro-oxidative, hence, NO level-reducing environment in the vascular wall of smokers is further facilitated by the deposition of oxidation catalyzing metals in cigarette smoke, as well as by an alteration in the balance between of oxidantgenerating and oxidant-reducing cellular systems, in favor of the former. 51,52 Macrophages, neutrophils, the mitochondrial respiratory chain, and xanthine oxidases are major sources of the increased levels of oxidants in the vascular wall of smokers. Furthermore, stable aldehydes in cigarette smoke increase reactive oxygen species production by the activation of NADPH oxidases.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…[53][54][55] Smokers further exhibit reduced levels of selenium, a central element in many antioxidant systems. 51 The shift to a vascular pro-oxidative state not only reduces NO levels but may also significantly contribute to lipid oxidation, 50,56 foam cell formation, foam cell death, and inflammation. Inflammation and oxidation are central elements in the activation of several CVD-relevant cell types, such as macrophages, endothelial cells, and platelets.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…[40][41][42] As was shown by our study and others smoking is more prevalent in obese patients which can contribute to the systemic inflammatory response and account for relatively higher AF recurrence rates post RF ablation. [43][44][45] As is well described in cardiomyopathy of obesity, gradual accumulation of adipose tissue among muscle fibers with pressure-induced atrophy , lipotoxicity and myocyte apoptosis in combination with above pro AF milieu can promote negative atrial remodeling and arrhythmogenecity. [46][47] Several studies in the past have shown significant correlation between OSA, obesity and AF.…”
Section: Journal Of Atrial Fibrillation Original Researchmentioning
confidence: 99%
“…23 The risk is 7.6 for non-smokers who are homozygous for the CFH Y402H polymorphism. 23 Smoking is a pro-oxidative factor, 24 and it is associated with a lower level of macular pigment (MP) optical density (infra vide). 25,26 Plasma nicotine activates retinal phospholipase A2, leading to the formation of arachidonic acid, a precursor of prostaglandins, and various cytokines, which are inflammatory mediators.…”
Section: Smokingmentioning
confidence: 99%